Effectiveness of Movement Learning in Children: The Role of Developmental Maturity (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
This study investigated whether structured movement programs work differently for children at varying developmental levels using a 2×2 factorial quasi-experimental design with pretest-posttest measurements. Forty-eight children aged 5-6 years from an Islamic Kindergarten in Kuningan Regency were assigned to groups using intact classroom placement (no individual randomization). Developmental maturity was operationalized through age-based classification, including low maturity (5.0-5.5 years) and high maturity (5.6-6.0 years). The four-week intervention (eight 45-minute sessions) compared structured versus conventional activities across maturity levels. Motor skills were assessed using the Test of Gross Motor Development Third Edition (TGMD-3), while motivation, confidence, and understanding of physical activity were measured using an adapted early-childhood physical literacy questionnaire (α = .81). Results showed that while structured programs benefited everyone, their impact on motor skills varied significantly by maturity level (F=15.89, p.001), with more mature children gaining greater advantages. Interestingly, benefits for motivation and confidence were similar across maturity levels. Within the limitations of this single-site study, the findings suggest that educators should implement structured movement programs while recognizing that motor skill benefits may vary according to developmental maturity, whereas affective outcomes, such as motivation and confidence, develop similarly across maturity levels.